Building a multicultural peer-consultation team: Planning, implementing, and early sustainment evaluation. (December 2022) - Nagy, Gabriela A.; Cassiello-Robbins, Clair; Anand, Deepika; Arnold, Macey L.; Coleman, Jessica N.; Nwosu, Joshua; Singh, R. Sonia; Woodward, Eva N.
This article represents an implementation-focused evaluation of a multicultural peer-consultation team situated within a psychiatry department in a large academic medical center in the Southern United States. The evaluation comprised anonymous self-report questionnaires ( n = 14) as well as individual ( n = 3) or group interviews ( n = 10) conducted by outside independent evaluators. Participants were current and former team members (i.e., graduate trainees, mental health care providers, clinical and research staff members) who voluntarily participated in this multimethod implementation evaluation. Results indicated that attendance on the team had several important impacts on members, and most notably an increased ability to provide multiculturally competent care, that is treatment that carefully and routinely considers the influence of culture and context on patients and therefore their clinical presentation. Further, no negative impacts from participating on the team were noted. A primary strength of the team's sustainability is that participation on the team was deemed to be relevant and useful by current and former team members. A major barrier to participation on the team is competing demands, such as high clinical loads. We conclude that this model for multicultural peer-consultation holds promise as an effective and implementable educational method for mental health care professionals. We discuss strengths, limitations, and future directions for research.